Perspectives from leadership and frontline staff on telehealth transitions in the Los Angeles safety net during the COVID-19 pandemic and beyond - Casillas, Alejandra; Valdovinos, Cristina; Wang, Elizabeth; Abhat, Anshu; Mendez, Carmen; Gutierrez, Griselda; Portz, Jennifer; Brown, Arleen; Lyles, Courtney R. (Frontiers in Digital Health, 2022)
Objectives: The start of the COVID-19 pandemic led the Los Angeles safety net health system to dramatically reduce in-person visits and transition abruptly to telehealth/telemedicine services to deliver clinical care (remote telephone and video visits). However, safety net patients and the settings that serve them face a “digital divide” that could impact effective implementation of such digital care. The study objective was to examine attitudes and perspectives of LAC DHS leadership and frontline staff regarding telehealth integration in the Los Angeles safety net, with a focus on telemedicine video visits. Methods: This qualitative study took place in the Los Angeles County Department of Health Services (LAC DHS), the second-largest safety net health system in the US. This system disproportionately serves the uninsured, Medicaid, racial/ethnic minority, low-income, and Limited English Proficient (LEP) patient populations of Los Angeles County. Staff and leadership personnel from each of the five major LAC DHS hospital center clinics, and community-based clinics from the LAC DHS Ambulatory Care Network (ACN) were individually interviewed (video or phone calls), and discussions were recorded. Interview guides were based on the Consolidated Framework for Implementation Research (CFIR)), and included questions about the video visit technology platform and its usability, staff resources, clinic needs, and facilitators and barriers to general telehealth implementation and use. Interviews were analyzed for summary of major themes. Results: Twenty semi-structured interviews were conducted in August to October 2020. Participants included LAC DHS physicians, nurses, medical assistants, and physical therapists with clinical and/or administrative roles. Narrative themes surrounding telehealth implementation, with video visits as the case study, were identified and then categorized at the patient, clinic (including provider), and health system levels. Conclusions: Patient, clinic, and health system level factors must be considered when disseminating telehealth services across the safety net. Participant discussions illustrated how multilevel facilitators and barriers influenced the feasibility of video visits and other telehealth encounters. Future research should explore proposed solutions from frontline stakeholders as testable interventions towards advancing equity in telehealth implementation: from patient training and support, to standardized workflows that leverage the expertise of multidisciplinary teams.